Eltrombopag can overcome the anti-megakaryopoietic effects of lenalidomide without increasing proliferation of the malignant myelodysplastic syndrome/acute myelogenous leukemia clone. Issue 12 (December 2014) - Tamari, Roni; Schinke, Carolina; Bhagat, Tushar; Roth, Michael; Braunschweig, Ira; Will, Britta; Steidl, Ulrich; Verma, Amit
Abstract Lenalidomide (Len) is clinically indicated in myelodysplastic syndrome (MDS) but its use is limited by significant thrombocytopenia. Eltrombopag (EP) is a thrombopoietin receptor agonist that can stimulate platelet production and has shown preclinical efficacy in inhibiting leukemic cell proliferation. Thus, we determined the preclinical efficacy and safety of combining Len and EP in acute myelogenous leukemia (AML) and MDS. We found that single agent treatment of leukemia and lymphoma cell lines with EP and Len showed differential sensitivities to either agent. Combination therapy did not result in reversal of anti-malignant effects on these cells. Furthermore, the combination of Len and EP resulted in significant inhibitory effects on growth of leukemic colonies in the majority of primary MDS and AML samples. Most importantly, EP was able to reverse the anti-megakaryopoietic effects of Len in primary MDS patient samples. These results provide a preclinical rationale for the use of this combination in MDS and AML.